Apoptosis inducer from Streblus asper extracts for cancer chemoprevention - Seeni, Azman; Zulkepli, Nur Ayunie; Abdul Wahab, Ridhwan (Springer, 2012)
One of the approaches to control cancer is prevention through consumption of fruits and vegetables which are associated with a reduced risk of cancer. The present study was undertaken to examine the chemopreventive effects of Streblus asper root extracts on osteosarcoma (HOS) and tongue carcinoma (SCC-15) cells’ growth, cell cycle modulation, apoptosis induction, and associated molecular alterations in vitro . S. asper root extract treatment on HOS and SCC-15 cells resulted in a signi fi cant decreased in cell growth with IC 50 value of 0.3 and 1%, respectively which was associated with the cell cycle phase arrest and the induction of apoptosis. Cell cycle analysis showed G2/M phase arrest in HOS and G0/G1 phase arrest in SCC-15 cells following treatment with S. asper root extracts for 72 h. This S. asper -mediated cell cycle arrest in HOS cells was accompanied with a decrease in protein levels of phosphorylated ERK ½. Induction of apoptosis was characterized by the appearance of cells with sub-G1 DNA content and the cleavage and activation of caspase 3, caspase 9 and Bcl-2 proteins. Treatment with S. asper root extract also resulted in alterations of cell morphology including cell shrinkage, vacoularization, and membrane blebbing. These fi ndings show that S. asper modulates caspase dependent pathways for inhibition of cell growth and proliferation. The extract also did not demonstrate a mutagenic effect under the condition of the test with S. typhimurium and is not considered a mutagen. The results support the use of S. asper root extract in view of the therapeutic potential and help to elucidate the reasons underlying its potentiality as chemopreventive agents.